The radiologic features of intestinal capillariasis - Pojchamarnwiputh S. (2014)
Purpose: To demonstrate the radiologic findings in intestinal capillariasis. Material and methods: From 1996 to 1998, the clinical data and radiologic findings of three patients who were diagnosed as having intestinal capillariasis were reviewed retrospectively. The diagnosis of capillariasis was confirmed by finding ova and/or adult C. philippinensis from fecal examination. Results: All three patients presented with chronic watery diarrhea and weight loss for 4 months to 2 years before the diagnosis (mean 13.3 months). Two patients were female and one was male. Their mean age was 26.7 years (range 20-32 years). All three patients lived in the provinces of northern Thailand. The small bowel follow-through (SBFT) examination showed a malabsorption pattern, which was serve at the ileum. After treatment, all three patients improved clinically. In the follow-up SBFT study, two cases revealed near to normal findings. Conclusion: In endemic areas where patients have a history of chronic watery diarrhea associated with radiologic findings of a malabsorption pattern, intestinal capillariasis should be included in the differential diagnosis.